EVALUASI KEPUASAN MAHASISWA TERHADAP KUALITAS LAYANAN AKADEMIK FAKULTAS TARBIYAH DAN KEGURUAN UNIVERSITAS ISLAM NEGERI AR-RANIRY BANDA ACEH - Maria Ulfa; Rahmat Musfikar; Sri Wahyuni; Hendri Ahmadian (JINTECH: Journal Of Information Technology, 2022)
: The purpose of this study is to find out the results of student satisfaction with the services provided by the academics of the Faculty of Tarbiyah and Teacher Training (FTK) at Universitas Islam Negeri Ar-Raniry Banda Aceh seen from 5 service dimensions. The sample of this study was 100 active students from the 2016-2020 class using the quota sampling technique, which is to determine a sample from a certain population so that it is classified as desired. Research data was obtained by distributing questionnaires through online media (google form) which contained 25 question items. Data analysis using simple linear regression analysis method. Results The level of student satisfaction in FTK. Services at FTK have been carried out quite well so that students are satisfied with the services from the dimensions of reliability, responsiveness, assurance and empathy. Then in the tangibles dimension, students prefer to meet academic officers with 61% of respondents' answers. And the question item Academic services provided are computer-based with an answer of 70% meaning that students are very satisfied if the service is computer-based. The quality of academic services has an influence on student satisfaction where the results of the analysis of the level of conformity are 46%.